2010
DOI: 10.1021/ol1006955
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of α-Methylene-β-hydroxy Carboxylic Acid Derivatives via a Diastereoselective Aldol/β-Elimination Sequence: Application to the C(15)−C(21) Fragment of Tedanolide C

Abstract: An enantioselective synthesis of α-methylene-β-hydroxy carboxylic acid derivatives via a highly diastereoselective, one-pot syn-aldol and β-elimination sequence utilizing the chiral β-(phenylselenyl)propionyl imide 15 is described. This new method, which constitutes an alternative to the Baylis-Hillman reaction, has been applied to the synthesis of the C(15)-C(21) fragment of tedanolide C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…B. alloc, MMTr) richtete sich unser Augenmerk auf die Arbeiten von Roush, der über die selektive Schützung der C17‐OH‐Gruppe als TES‐Ether berichtete. Unter Verwendung dieser Arbeitsvorschrift konnten wir schließlich die C17‐OH‐Gruppe von 11 8a,b mit TESCl bei −78 °C erfolgreich schützen. Die Behandlung mit DDQ unter wasserfreien Bedingungen lieferte schließlich das entsprechende PMP‐Acetal, das mit DIBAL‐H regioselektiv geöffnet werden konnte (Schema ).…”
Section: Methodsunclassified
“…B. alloc, MMTr) richtete sich unser Augenmerk auf die Arbeiten von Roush, der über die selektive Schützung der C17‐OH‐Gruppe als TES‐Ether berichtete. Unter Verwendung dieser Arbeitsvorschrift konnten wir schließlich die C17‐OH‐Gruppe von 11 8a,b mit TESCl bei −78 °C erfolgreich schützen. Die Behandlung mit DDQ unter wasserfreien Bedingungen lieferte schließlich das entsprechende PMP‐Acetal, das mit DIBAL‐H regioselektiv geöffnet werden konnte (Schema ).…”
Section: Methodsunclassified
“…After unsuccessful experimentation with various protecting groups (e.g., alloc, MMTr) our attention was caught by a method published by the Roush group, which reported the selective protection of the C17 hydroxy group as the TES ether. By following their protocol, selective protection at the C17 hydroxy group of 11 8a,b was accomplished through treatment with triethylsilyl chloride. Subsequent treatment with DDQ under anhydrous conditions generated the corresponding PMP acetal, followed by regioselective reductive acetal opening with DIBAL‐H (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on studies performed with radioactively labeled derivatives of tedanolide,F usetani confirmed that tedanolide (1)b inds to the 60S ribosomal subunit. [2,5 ] Thes tructural complexity of tedanolides has attracted the attention of several research groups, [6] with total syntheses put forward by the groups of Smith, [7] Roush [8] and Kalesse. [9] Thes ignificant structural characteristics of the tedanolides are an 18-membered macrolactone and an epoxide on the side chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a non-aldol-strategy for such tertiary alcohols was put forward by Roush and Barth in the course of their efforts towards tedanolide C. They used a Sharpless asymmetric dihydroxylation of an advanced intermediate to establish the required tertiary and primary alcohol moieties. 6 In contrast to the above mentioned aldol strategies, enolates of αoxygenated carbonyl compounds can react with nearly all aldehydes. Both of these approaches can be performed with enol ethers or ketene acetals.…”
Section: Introductionmentioning
confidence: 99%